Frank Zappa FAQ : all that's left to know about the father of invention - Corcelli, John (FAQ series (Applause Theatre & Cinema Books (Firm)), 2016)
"In this volume, author John Corcelli reveals Zappa's roots as a musician, from his diverse influences to his personal life. We also learn more about his former band members and the enormous musical legacy inherited by his son, Dweezil. The book features a juried examination of Zappa's recordings and his videos. It also features a complete discography and a recommended reading list. Each chapter has a special focus on Zappa's life, with sections covering his family, his home studio known as the Utility Muffin Research Kitchen his keen interest in the Synclavier (a device he first used in 1980), his guitars, and more. Special attention is paid to the Mothers of Invention. Frank Zappa FAQ is a must-have for fans new and old looking to delve into some of the best music ever made by one of the most innovative artists the world has known."--Publisher description.